2012
DOI: 10.1071/en12131
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Sydney dust storm and its mineralogical and organic characteristics

Abstract: Environmental context. In 2009, at the end of the longest drought period ever recorded in Australia, a major dust storm blanketed the cities of Sydney and Brisbane for more than 24 h. The source of the dust was inner New South Wales and South Australia, where large scale open-cut mining occurs together with agricultural practices. We report results of extensive mineralogical and chemical analyses of the dust, and discuss their significance in terms of the dust origins and potential human health risks.Abstract.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…In particular, although it is clear that substantial amounts of organic material can be found in dust aerosols emitted from fertile soils (e.g. Vega et al, 2001;Aryal et al, 2012;Chow et al, 2003;Rutter et al, 2011), budgets for mineral-dust-associated organic matter emitted into the atmosphere from soils have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, although it is clear that substantial amounts of organic material can be found in dust aerosols emitted from fertile soils (e.g. Vega et al, 2001;Aryal et al, 2012;Chow et al, 2003;Rutter et al, 2011), budgets for mineral-dust-associated organic matter emitted into the atmosphere from soils have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…During the period of study, a major dust storm occurred in September 2009 during the Australian Millennium drought (Aryal et al, 2012). Although dust storms occur frequently and lead to dust deposition and surface layer nutrient enrichment (Gabric et al, 2010), the September 2009 event is the only one associated with a significant maximum in the Chl-a concentration across the whole of the study region.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…In this context, Aryal et al (2012) characterised the mineralogy and organic matter present in an atmospheric deposition sample collected in Sydney during the same 2009 dust storm. The analysis found that the dust storm contained aluminium and silicon along with around 10.6% organic carbon on weight basis.…”
Section: Introductionmentioning
confidence: 99%